Loss of liver kinase B1 in human seminoma - Kumar, Manish; Sahoo, Subhransu S.; Jamaluddin, M. Fairuz B.; Tanwar, Pradeep S. (Frontiers in Oncology, 2023)
Testicular cancer is a common malignancy of young males and is believed to be originated from defective embryonic or adult germ cells. Liver kinase B1 (LKB1) is a serine/threonine kinase and a tumor suppressor gene. LKB1 is a negative regulator of the mammalian target of rapamycin (mTOR) pathway, often inactivated in many human cancer types. In this study, we investigated the involvement of LKB1 in the pathogenesis of testicular germ cell cancer. We performed immunodetection of LKB1 protein in human seminoma samples. A 3D culture model of human seminoma was developed from TCam-2 cells, and two mTOR inhibitors were tested for their efficacy against these cancer cells. Western blot and mTOR protein arrays were used to show that these inhibitors specifically target the mTOR pathway. Examination of LKB1 showed reduced expression in germ cell neoplasia in situ lesions and seminoma compared to adjacent normal-appearing seminiferous tubules where the expression of this protein was present in the majority of germ cell types. We developed a 3D culture model of seminoma using TCam-2 cells, which also showed reduced levels of LKB1 protein. Treatment of TCam-2 cells in 3D with two well-known mTOR inhibitors resulted in reduced proliferation and survival of TCam-2 cells. Overall, our results support that downregulation or loss of LKB1 marks the early stages of the pathogenesis of seminoma, and the suppression of downstream signaling to LKB1 might be an effective therapeutic strategy against this cancer type.